Technical Efficiency of Polish Independent Public Health Care Centres: Data Envelopment Analysis Approach - Joanna Podgórska (Barometr Regionalny, 2018)
In the face of the growing demand for health services, which can be observed in Poland (as well as in many other countries), it is extremely important to make effective allocation decisions in relation to financial resources (at the disposal of health sector decision-makers). The pace of demographic, technological and market changes forces an increase in financial expenditures on health, while at the same time the resources allocated to these objectives are still lacking. The present paper assesses the technical efficiency of 24 independent public health care centers (IPHCCs) in 2010–2014 with the use of the data envelopment analysis method and evaluates changes in the examined efficiency categories using the Malmquist Index. The research has shown that independent public health care institutions in Poland are facing the problem of debt and inefficiency. It has also been established that the level and method of financing health services in Poland contribute to a large extent to the technical inefficiency of IPHCCs, and that the increase in IPHCCs’ revenues leads to an increase in their technical efficiency. The conclusions of this paper provide, on one hand, the basis for in-depth research into the efficiency of public health entities and, on the other, guidance that can be used in the practical management of public health entities and in the shaping of national health care policy.